Comparative toxic effects of copper-based nanoparticles and their microparticles in Daphnia magna by using natural freshwater media. Issue 3 (3rd July 2019) - Arratia, Francisca; Olivares-Ferretti, Pamela; García-Rodríguez, Alba; Marcos, Ricard; Carmona, Erico R.
ABSTRACT: Copper-based nanoparticles (NPs) are being widely used in different application fields and their health impacts to aquatic environments represent a current concern. Few studies are available about their comparative toxicity with their bulks and ions under natural exposition in aquatic organisms. Thus, the toxicity of Cu and CuO NPs and their microparticle and ionic forms was assayed in the acute immobilisation test of Daphnia magna by using freshwater media. Electronic microscopy, laser doppler velocimetry, and dynamic laser scattering methodologies were used to NPs characterisation. The results indicated that CuNPs and CuONPs were more toxic than their microparticles. Among NPs, CuNPs showed higher toxicity than CuONPs. Copper-based nanoparticles showed similar hydrodynamic particle size and were agglomerated in culture media, suggesting toxic-ionic release relationship and corroborated by the high toxicity induced by CuSO4 . Additionally, water chemistry of natural freshwater used in the experiments also favoured the ion release of these NPs.